Characterization of Sound Absorption Coefficient and Acoustic Impedance of Palm Frond Fiber Composites with Pine Resin on Various Composition Variations - Putri Pratiwi; Asmara Yanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2023)
This research aims to investigate the ability of sound absorption coefficient and the acoustic impedance of Palm Frond Fiber Composites using the one-microphone impedance tube method. We used Palm Frond Fibers as a filler and pine resin as an alternative adhesive of composite with a volume fraction of 50%: 50%, 60%: 40%, 70%: 30%, 80%: 20%, and 90%: 10%. The sound absorption coefficient and acoustic impedance of composites were studied at 500, 1000 Hz, 1500 Hz, 2000 Hz, and 2500 Hz frequency. The results showed that the highest sound absorption coefficient was found in 1500 Hz frequency and using volume fraction 70%:10%. The highest acoustic impedance response was found in composite with a fiber composition of 90% and at the test frequency with a range of 500 Hz -1500 Hz. The composition of the adhesive and fiber greatly affects the impedance value because it was related to the formation of pores in the composite. Based on ISO standard 11654:1997, the value of the sound absorption of sound waves was 0.15, and Palm Frond Fiber had a value above, so it had the potential used as sound absorption material.